Overexpression of 14-3-3γ Induces the Migration and Invasion of Human Lung Adenocarcinoma A549 Cells - Raungrut, Pritsana; Champoochana, Nidanut; Thongsuksai, Paramee; Promnares, Kamontip (Journal of Health Science and Medical Research, 2022)
Objective: 14-3-3 gamma (γ) is known to modulate the development and progression of many cancers. However, the evidence in lung cancer is still unclear. In this study, effects of 14-3-3γ on tumor cell migration and invasion were investigated. Material and Methods: A 14-3-3γ expression vector was made and transfected into A549 cells. In-vitro scratch assay and transwell assay were applied to assess migration and invasion, respectively. Western blotting was used to detect expression of proteins related to epithelial–mesenchymal transition. Results: Closing rate of scratch wounds, both in classical and non-classical scratch assay, was significantly increased in 14-3-3γ-overexpressing cells in comparison to the controls. Similarly, by transwell assay, a significant increase in the invasion and migration was shown in the 14-3-3γ-overexpressing cells in comparison to the null vector cells, by approximately 79.2% (p-value=0.002) and 131.2% (p-value<0.001), respectively. In addition, increased 14-3-3γ expression resulted in a significant increase of β-catenin and Snail but not for E-cadherin and vimentin. Conclusion: The study demonstrates the role of 14-3-3γ protein on lung cancer progression via migration and invasion processes, possibly providing a new targeted therapy for non-small cell lung cancer.